TRANSFORMASI DIGITAL UMKM PERCETAKAN: OPTIMALISASI PLATFORM ECOMMERCE TERINTEGRASI PADA ESPRINT.STORE - Muhammad Nabil Musyarof; Afif Kisnandhya Putra; Nibroos Naufal Islam; Rizky Dwi Astuti; Kartika Imam Santoso; Andri Triyono (Julia: Jurnal Ilmu Komputer An Nuur, 2025)
Digital transformation has become a strategic necessity for Micro, Small, and Medium Enterprises (MSMEs), particularly in the printing sector which demands speed, flexibility, and personalized services. This study aims to examine the effectiveness of the esprint.store platform as a web-based eCommerce solution integrated with WhatsApp API and a dynamic pricing system. A mixed-method approach was employed, combining Google Analytics data, a System Usability Scale (SUS) questionnaire from 120 respondents, and system architecture observation. The results indicate a 35% increase in sales conversion and a reduction in customer response time from 24 hours to 15 minutes. These findings suggest that digitalization through a simple yet functional system can enhance service efficiency and customer satisfaction within the MSME.